Insider's guide to school leadership : - Goldberg, Mark F. (Jossey-Bass, 2006)
This guide for administrators focuses on various aspects of school leadership focusing on staff, students, and personal skills. Using his own experiences and ideas from interviews with administrators across the US, Goldberg describes recruitment, retention, the safety and emotional well-being of students, maintaining professional knowledge, meetings, staff development, leadership, charisma and creativity, supervision, statistical data, and communication with the parents and community. The book is set up in the format of three to nine "rules" per chapter, with descriptions and bullet points. No bibliography is provided.